Green Tourism-Based Food and Beverage Service to Increase Customer Satisfaction at Four Points By Sheraton Bali Kuta - Ni Kadek Agustini; Made Sudiarta; Ida Ayu Elistyawati; I Nyoman Winia; I Ketut Suparta (Yayasan Sinergi Widya Nusantara, 2023)
Purpose: This study to determine the application of green tourism based service by the food and beverage service department at Four Points By Sheraton Bali Kuta and how it impact on customer satisfaction. Research methods: The research sample was determined by the incidental sampling method with a sampe of 80 guest who had received service from the food and beverage service department at Four Points By Sheraton Bali Kuta as respondents. The data collection method used in a questionnaire. The data analysis technique is descriptive qualitative analysis with descriptive statistics on a likert scale range using microsoft excel 2010. Findings: The results show that the application of green tourism-based services on green service and energy-saving variables according to customers is not good. The variables of green product, green design and consumption reduction according to customers are good. Implications: The impact of green tourism-based services on customer satisfaction at The Eatery Restaurant is that customers agree to take actions such as buying back products and services, recommending products and services to others, buying other types of products from The Eatery Restaurant, being interested in buying food and beverage products from The Eatery Restaurant.